Analisis Penerapan Rekam Medis Elektronik pada Klinik Utama Bunafsi di Kabupaten Wonogiri - Bayu Rusmadi Putra; Rosyidah Rosyidah; Widodo Hariyono (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Electronic Medical Records (RME) is a technology that is a priority in the development of health information systems. RME has significant benefits in patient data management, medication management, and clinical management. However, the implementation of RME at the BUNAFSI Main Clinic in Wonogiri Regency still needs to be carried out in a structured and systematic manner. This research is to determine the application or implementation based on 8 activities carried out in the electronic medical record system at the BUNAFSI Clinic in Wonogiri Regency, namely: how to implement patient registration, how to distribute patient medical record data, how to fill in clinical information on patient data, how to processing electronic medical record information on patient data. What is the data input process for financing claims? What is the process for storing patient data medical records? How is quality assurance of electronic medical records implemented? What is the process for transferring the contents of electronic medical record patient data?. The research method used is a qualitative research method. In this analysis, data was collected through observation and descriptive analysis methods. Data is obtained from various sources, such as financial reports, statistical reports, and reports from doctors and nurses. The results of the analysis show that the implementation of RME at the BUNAFSI Main Clinic in Wonogiri Regency still has several obstacles. Some of the obstacles include difficulties in managing patient data, difficulties in managing drugs, and difficulties in clinical management. This analysis shows that the implementation of RME at the BUNAFSI Main Clinic in Wonogiri Regency still needs to be carried out in a structured and systematic manner. To overcome these obstacles, support is needed from the government, management, and doctors and nurses. Keywords: Electronic Medical Records, RME, Application of RME  ABSTRAK Rekam Medis Elektronik (RME) merupakan salah satu teknologi yang menjadi prioritas dalam pengembangan sistem informasi kesehatan. RME memiliki manfaat yang signifikan dalam pengelolaan data pasien, pengelolaan obat, dan pengelolaan klinis. Tetapi, penerapan RME di Klinik Utama BUNAFSI di Kabupaten Wonogiri masih perlu dilakukan secara terstruktur dan sistemati. Penelitian ini adalah mengetahui penerapan atau pelaksanaan berdasar pada 8 kegiatan yang dilakukan dalam sistem rekam medis eleketronik di  Klinik  BUNAFSI di Kabupaten Wonogiri, yaitu:bagaimana penerapan registrasi pasien, pelaksanaan distribusi data rekam medis pasien, Bagaimana proses pengisisan informasi klinis data pasien, Bagaimana pengolahan informasi rekam medis elektronik data pasien, Bagaimana proses penginputan data untuk klaim pembiayaan? Bagaimana proses penyimpanan rekam medis data pasien? Bagaimana pelaksanaan penjaminan mutu rekam medis elektronik? Bagaimana proses transfer isi rekam medis elektronik data pasien?. Metode penelitian yang digunakan adalah metode penelitian Kualitataif. Dalam analisis ini, dilakukan pengumpulan data melalui metode observasi dan analisis deskriptif. Data diperoleh dari berbagai sumber, seperti laporan keuangan, laporan statistik, dan laporan dari para dokter dan perawat. Hasil analisis menunjukkan bahwa penerapan RME di Klinik Utama BUNAFSI di Kabupaten Wonogiri masih ada beberapa kendala. Beberapa kendala antara lain adalah kesulitan dalam pengelolaan data pasien, kesulitan dalam pengelolaan obat, dan kesulitan dalam pengelolaan klinis. Dalam konklusi, analisis ini menunjukkan bahwa penerapan RME di Klinik Utama BUNAFSI di Kabupaten Wonogiri masih perlu dilakukan secara terstruktur dan sistematis. Untuk mengatasi kendala-kendala tersebut, diperlukan pendukungan dari pihak pemerintah, pihak manajemen, dan para dokter dan perawat. Kata Kunci: Rekam Medis Elektronik, RME,Penerapan RME